The Effect of Leadership Style, Competence and Motivation on Employee Performance Dinas Pengelolaan Bangunan and Tanah Kota Surabaya - Hany Rifky Eryanto; Elok Damayanti (Jurnal Ekonomi, 2020)
This study aims to analyze the influence of leadership style (X1), competence (X2) and motivation (X3) on employee performance (Y) at Dinas Pengelolaan Bangunan dan Tanah Kota. The sample was obtained by random sampling method with 100 respondents from 132 employees. The data analysis used in this research includes data quality test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of the partial significance test (t statistical test) from the analysis and discussion of the research show that leadership style, competence and motivation partially have a significant effect on employee performance and the simultaneous significance test (f test) of the analysis and discussion of the study shows that leadership style, competence and motivation together have a significant effect on employee performance at Dinas Pengelolaan Bangunan dan Tanah Kota Surabaya.